Hubungan Pengetahuan, Sikap, Dan Dukungan Suami Dengan Pemberian Asi Eksklusif Pada Pasangan Menikah Dini Di Wilayah Kerja Puskesmas Selo Boyolali Tahun 2017 - Rumiati, Fidya; , Yuli Kusumawati, SKM, M.Kes (Epid) (2017)
The number of early marriages in Selo is the highest in Boyolali District, which is 120 people in 2015. The high number of early marriages has an impact on female reproductive health as well as the increasing number of IMR (Infant Mortality Rate) and UMR (Underfive Mortality Rate) caused by malnutrition, one of them due to low exclusive breastfeeding. Exclusive breastfeeding coverage in Selo is only 48.3%, has not met the SPM goal 2015 Boyolali District. The purpose of this study was to analyze the relationship between knowledge, attitude, and husband support with exclusive breastfeeding in early married couples in the work area of Public Health Center Selo Boyolali in 2017. This type of research is observational uses analytic survey method with cross sectional design. The population in this study is all husbands of early married couples who had children aged 7-12 months at the time of study in the working area of Public Health Center Selo, with a minimum sample of 64 people. Sampling using total sampling. The analysis used Chi-square. The result of statistical test shows that there is a correlation between knowledge (p= 0,000), attitude (p= 0,000), and husband support (p= 0.009) in early married couples with exclusive breastfeeding in the work area of Public Health Center Selo Boyolali 2017.